Organizational-economic mechanism for the digitalization of the chemical industry - E. V. Kulyasova (Путеводитель предпринимателя, 2020)
The article substantiates the leading role of digitalization in creating conditions for increasing the competitiveness of enterprises of the Russian chemical complex. A three tier system of digitalization indicators is given: for individual enterprises, the industry and the economy as a whole, as well as the corresponding effects. The functions and relationships of the proposed organizational and economic mechanism for managing the digitization of the chemical industry are described. As organizational and economic impacts, the developed mechanism includes decisions on the adjustment of investment programs; participation in the formation of state tasks for educational institutions; identifying priorities for developers of solutions in the field of digitalization and the choice of strategies for disseminating the results of intellectual activity and a number of others.